2023
DOI: 10.3389/fbioe.2023.1148342
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of multiple pelvic screws and multirod construct for the augmentation of lumbosacral junction in long spinal fusion surgery

Abstract: Background: Posterior long spinal fusion was the common procedure for adult spinal deformity (ASD). Although the application of sacropelvic fixation (SPF), the incidence of pseudoarthrosis and implant failure is still high in long spinal fusion extending to lumbosacral junction (LSJ). To address these mechanical complications, advanced SPF technique by multiple pelvic screws or multirod construct has been recommended. This was the first study to compare the biomechanical performance of combining multiple pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Since the introduction of the Galveston iliac xation instrument in 1982, emerging sacroiliac xation techniques, such as sacral alar screws (SASs), have been recognized as reliable xation methods for lumbosacral internal xation surgery [34]. A su cient number of previous experimental and clinical results have demonstrated that SASs not only reduce the necessary motion inside the sacroiliac joint and enhance the stability of the fused segment but also alleviate biomechanical overload [34,35]. Therefore, we considered that the LP-PLSIF technique was the optimal choice for achieving stable long spinal fusion and signi cantly improving surgical e cacy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of the Galveston iliac xation instrument in 1982, emerging sacroiliac xation techniques, such as sacral alar screws (SASs), have been recognized as reliable xation methods for lumbosacral internal xation surgery [34]. A su cient number of previous experimental and clinical results have demonstrated that SASs not only reduce the necessary motion inside the sacroiliac joint and enhance the stability of the fused segment but also alleviate biomechanical overload [34,35]. Therefore, we considered that the LP-PLSIF technique was the optimal choice for achieving stable long spinal fusion and signi cantly improving surgical e cacy [33].…”
Section: Discussionmentioning
confidence: 99%
“…S2-Alar-Iliac (S2AI) or iliac screws can minimize the risk of both symptomatic L5/S1 pseudarthrosis and SIJ osteoarthritis. [52][53][54] SPF has the advantage of significantly reducing peak stresses at the L5/S1 segment. 55 However, because the SIJ is only transfixed with S2AI screws and only fixed with iliac screws, screw/rod breakage or screw loosening may occur depending on the preoperative extent of SIJ mobility.…”
Section: Dovepressmentioning
confidence: 99%